Stress concentration factors on glued joints of timber/ Rosiah Abu Samah - Abu Samah, Rosiah (1995)
The project comprises the Finite Element Analysis of the glued joint of timber under tensile loads with different tip thickness, slope and finger length. The analysis of the timber glued joint covers the single and mini finger joints. The failure of timber glued joint such as finger joint under tension load is not solely depends on effective area' of the cut section. The effect of notches and holes influenced the failure load due to the stress concentration besides the notches and holes. The stress concentration reduces the failure load of the timber glued joint. The stress concentration factor for the glued joint should be included in order to obtain a correct net strength of the glued joint: The coefficient of stress concentration can be determined with the finite element method as a two-dimensional elastic problem by analysing the maximum and minimum stresses around the joints. The modulus elasticity, E of the joint also can be obtained by analysing the displacement of the joint to get the stress-strain relationship. It is can be concluded that when the tip of finger joint increases the stress concentration factor decrease and therefore the tensile strength reduces.